Fibrosis‐Guided Ablation in Patients With Atrial Fibrillation: A Meta‐Analysis of Randomized Controlled Trials. - Salih, Ahmed; Sutaria, Aman; Montaser, Zeinab; Magar, Tony Pun; El Ashal, Gehad; Zaghloul, Sheref; Tom, Alen Jiji; Ahmad, Mahmood; Creta, Antonio; Ali, Hussam; Barra, Sergio; Farkowski, Michal; et al. (Journal of Cardiovascular Electrophysiology, 2025)
Ablation of fibrotic atrial regions has been suggested to improve the results of atrial fibrillation (AF) catheter ablation. We aimed to evaluate the efficacy and safety of fibrosis‐guided ablation in addition to pulmonary vein isolation (PVI) among AF patients undergoing ablation through a systematic review of randomized controlled trials. The review protocol was registered on PROSPERO (CRD42024561077). Database searches were conducted on EMBASE and MEDLINE until 6th September 2024. Freedom from atrial arrhythmia (including AF and/or atrial tachycardia) and periprocedural complications were the main outcomes. Twelve trials (total of 3,066 patients) were included in the analysis. Ten studies utilized three‐dimensional electroanatomic voltage mapping, and two used magnetic resonance imaging (MRI) to map atrial fibrosis. Compared to PVI, adjunctive fibrosis‐guided ablation significantly improved freedom from atrial arrhythmia (risk ratio [RR] 1.13; 95% confidence interval [CI] 1.04 − 1.23; p = 0.004; I² = 35%). This benefit was seen in persistent AF (RR 1.13; 95% CI 1.01 − 1.25; p = 0.03), but not paroxysmal AF (RR 1.16; 95% CI 0.83 − 1.61; p = 0.20). Only low‐voltage area ablation showed improved freedom from atrial arrhythmias (RR 1.17; 95% CI 1.06 − 1.28 vs. RR 1.03; 95% CI 0.80 − 1.32 using MRI‐voltage detection). A numerically, but nonsignificant, higher rate of periprocedural complications was observed with fibrosis‐guided ablation (4.4% vs. 2.8%; RR 1.44; 95% CI 0.82–2.56; p = 0.18) driven by the results of the DECAAF‐II trial. Fibrosis‐guided ablation, targeting low‐voltage areas on electroanatomic mapping, may be an effective adjunctive target to PVI for improving AF freedom, particularly for persistent AF. However, this approach poses safety concerns.